Competitividad en las empresas del sector transporte (Taxismo) en el cantón Latacunga - Añarumba Yanez, Katherine Liseth (2023)
The main objective of this research work is to determine how the factors affect the competitiveness of companies in the taxi sector in the Latacunga canton, where the problem lies in the lack of an efficient and quality service for its users, in addition to of vehicles that are in good condition, adding to this the increase in competition that is intense both nationally and locally, since in terms of taxis there is a high level of operators.